Industrially Purified Nd Materials Identified by Distinct Mass-Dependent Isotopic Composition - Bothamy, Nina; Galy, Albert (Frontiers in Environmental Chemistry, 2021)
Rare earth elements (REEs) are considered emerging anthropogenic pollutants. Anthropogenic lanthanum, cerium, samarium, and gadolinium alone, or excess of all the REEs have already been reported in the environment. In addition, it is only a matter of time for neodymium (Nd) of anthropogenic origin to be reported disseminated in the environment, given its growing demand for new technologies and its use in permanent magnets of wind turbine. So far, only in a few cases was the addition of anthropogenic Nd detected in soils and sediments by the measurements of REE concentrations. For this reason, we propose to use the Nd isotopic composition to help the distinction of pollution. The isotopic tracing of Nd using variations in the abundance of 143Nd from the radioactive decay of 147Sm (Nd-radiogenic composition) is one option. Here, we expand the Nd isotopic fingerprinting by the investigation of the stable Nd isotopic composition expressed as δxNd, the relative permil (%0) deviation from the isotopic composition of the pure Nd JNdi-1 reference standard. The measurement of δxNd used a MC-ICPMS (multi-collector inductively coupled plasma mass spectrometry) with sample-standard bracketing technique, allowing the determination of precise and accurate Nd isotopic variations. Our results show that Nd-magnets (Neo) and man-made purified Nd materials are not significantly different on average (respectively, δ148Nd of −0.105 ± 0.023 and −0.120 ± 0.141%0). More importantly, they are different from terrestrial rocks (δ148Nd of −0.051 ± 0.031%0). Moreover, the Nd-radiogenic composition of Neo can be highly variable, even when they come from a single supplier. In addition, the study of all Nd stable isotopic compositions demonstrates that irrespective of their natural origin (witnessed by their Nd-radiogenic composition), all Nd from rocks and man-made materials are related by mass-dependent isotopic fractionation laws. We also have defined a parameter, the Δ148−150Nd′, allowing the distinction of thermodynamic isotopic fractionation (the Δ148−150Nd′ is invariant) from kinetic isotopic fractionation (the Δ148−150Nd′ is negatively correlated with the δ148Nd). Such covariation is observed for anthropogenic materials that could be seen as small deficit in 150Nd (around 5 ppm/%0/amu), but too small to be consistent with nuclear field effect. On the other hand, the anthropogenic material defines a covariation in the Δ148−150Nd'–δ148Nd space in full agreement with the theoretical expectation from mass-dependent kinetic isotopic fractionation. The mass-dependent fractionation of Nd by chromatographic separation is also consistent with a kinetic isotopic fractionation. The purification of Nd from other light REEs by industrial processes involves chromatographic separation and, therefore, is likely to produce anthropogenic Nd with low values for δ148Nd associated with high values for Δ148−150Nd′. Both are resolvable with current MC-ICPMS technology and could be useful to trace incoming anthropogenic pollution in the environment. In soils, the combination of low values for δ148Nd with high values for Δ148−150Nd′ is likely to be an unambiguous pollution signal from the degradation in the environment of Neo or other industrial products, especially if this is associated with an Nd-radiogenic composition inconsistent with the surrounding rocks and soils. In contrast, the industrial residue of Nd purification could be characterized by high δ148Nd with low values for Δ148−150Nd′, and the leak or the discharge of such residue could also be unambiguously distinguished.